Moralitas Tokoh dalam Novel Diktha dan Hukum Karya Dhia'an Farah - Anita Kurnia Rachman; Endang Sumarti; Kingkin Puput Kinanti (IKIP Budi Utomo Malang, 2022)
Literary works are creative products born through the author's imagination through a touch of thoughts and ideas. Literary development not only provides entertainment and beauty for readers but also provides knowledge about literary values, such as moral, educational, social, and religious values. The purpose of this study is to determine the morality of the character who has descriptive and normative norms in the novel Dikta & Law by Dhia'an Farah. This research is a literature review research using a content analysis research model. The source of research data comes from a novel entitled Dikta & Law by Dhia'an Farah. This novel was published in 2021 with a total of 388 pages published by Asoka Aksara Loveable. Data collection techniques in this study, namely reading and note-taking techniques. The novel Dikta & Hukum is read as a whole carefully and repeatedly, especially on matters that contain morality. The reading activity was followed by marking certain parts according to the research focus. The results of this study produce character morality related to the teachings of parents which are applied in life, honesty, discipline, and responsibility.